THE ROLE OF ROLES AND CARDS WITH QUALITY OF SERVICE POSYANDU UNDERSTAND OF HEALTH STRATA IN SUMBERJO VILLAGE PURWOASRI DISTRICT KEDIRI DISTRICT - Siti Asiyah Siti Asiyah Siti Asiyah (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2016)
Toddler's integrated health service there are several strata, one of them is strata madya. The demands of quality services also apply to these strata of integrated health center. It depends the role of integrated health center cadre's in achieving better quality services. The objective of this research was to know the correlation of the role of cadre with quality service of toddler's integrated health center strata madya in village of sumberjo district of Purwoasri, kediri regency 2015.The research design was Analytic correlational with approach of cross sectional. The population was all toddler's mothers who visit integrated health center village of sumberjo, district of Purwoasri kediri regency amounted to 203 people with sample amounted to 67 respondents taken with technique of proportional cluster random sampling. The independent variable was role of the cadre and the tied of service quality that collected by questionnaire. Data expressed in ordinal scale and analyzed by Spearman correlation test.Based on the research results obtained that almost half of the respondents considered that the role of the integrated health center cadre in a good category amounted to 32 respondents (47.8%), the majority of respondents considered that the quality of integrated health center service tin enough category amounted to 36 respondents (53.7%) of the total 67 respondents and there was correlationthe role of cadre with service quality of toddler integrated health center strata madya (spearman: p value = 0,000 <0,05 then Ho was refused and H1 was accepted). Level of correlation was categorized as quite strong and positive (correlation coefficient: + 0.704), mean that the better assessment of the role of the integrated health center cadre's, the assessment of service quality at the most, also in a good category and vice versa. This is due to the realization of a good assessment toward the role ofcadres, then the officers was demanded to carry out their duties as well as possible.Thus, if the cadre's of toddler's integrated health center can display a good role then the quality of services provided is also satisfactory to the patient or customer will illlinediately give a good assessment toward f the role of cadres in integrated health center